(untitled) - Igarashi, Eikichi (Tokyo, 1906)
Baron Shibusawa's Preface: It is superfluous to say that a statesman must first of all possess a thorough knowledge of the finacial resources of his country before undertaking the grave task of arranging its financial and economic policy
Keywords: Tài chính,Finance; Nhật bản,Japan